The U.S. Imperial Jugger-not: Saturation Points and Cultural Globalization. - Bertoni, Meg Spohn (Integral Review: A Transdisciplinary & Transcultural Journal for New Thought, Research, & Praxis, 2010)
Globalization is not merely inevitable western cultural conquest. The assumption that the juggernaut of western hegemonic domination will continue until the world is consumed is a common one, but not an accurate one. That accuracy is compromised by a number of related misconceptions about the nature of globalization. Some of these have to do with an attachment to dichotomy in a world too complex for dualism. Some of them are related to assumptions about the nature of trade, of trends, of inevitability, and of statistical prediction that turn out not to be accurate-and by extension misconceptions about the unidirectionality of cultural exchange. Most are related to misconceptions about the nature of culture--particularly in oversimplifying, and making strange assumptions about, nonwestern cultures. Cultures change over time, with generations and historical forces--today's cultural changes make up tomorrow's cohesive culture. Cultures die not when they change to reflect the new attitudes and lifestyles of the peoples who live in them, but when they stagnate and become static, preserved only in museums, artifacts and books, and not in the everyday lives of the people themselves. Finally, phenomena do reach a saturation point, from biological populations to the motion of catamarans to absorption of cultural values, and these can be observed using methods of nonlinear dynamics. This project considers common misconceptions about globalization and culture, and uses concepts from nonlinear dynamics to expose the nature of the movement and saturation points of cultural globalization.